PROMOTING DOCTOR-PATIENT COMMUNICATION IN MEDICAL ENGLISH CLASSROOM THROUGH VIDEO AS PRE- ACTIVITY - Muhammad Rudy (Universitas Teknokrat Indonesia, 2023)
The three learning stages in a Flipped classroom have allowed the teachers to provide videos by creating them themselves or downloading them from other resources. Through multimodality, the present study explores a video that is considered suitable to apply in the pre-class activity stage. The multi-track analysis was adapted to seek verbal and non-verbal elements of the video for flipped classroom process. The result indicated that the doctor's semantics and gestures depicted the patient-centered model. Although minor errors existed, they became an unseen flaw of the video. Furthermore, it is suggested that medical English teachers use the video as a pre-class activity to show the ideal model for teaching doctor-patient communication.